Evaluating bioactive constituents and toxicological effects of aqueous extract of fermented Pentaclethra macrophylla seeds in rats - Eziuche Amadike Ugbogu; Chukwumaobim Daniel Nwoku; Victor Chibueze Ude; Okezie Emmanuel (Mashhad University of Medical Sciences, 2019)
Objective: This study aimed at evaluating the bioactive constituents and the toxicological profile of the aqueous fermented seed extract of P. macrophylla. Material and Methods: The chemical constituents of fermented P. macrophylla were assessed using GC-MS. For acute toxicity study, one-time doses of up to 5000 mg/kg of the extract were orally administered to male and female rats whereas 200, 400 and 800 mg/kg of the P. macrophylla extract were orally administered daily for 14 days in sub-acute toxicity investigation. Biochemical, haematological and lipid profiles were assessed following standard methods. Results: Bioactive compounds such as citronellol and oxirane, tetradecyl- (hexadecylene oxide) were identified in the extract. In acute toxicity test, no death or sign of toxicity was identified. For sub-acute study, ALT decreased significantly (p<0.05) while HDL-C had dose-dependent increases. No effect (p<0.05) on haematological parameters except on platelets was found. No histopathological changes were observed. Conclusion: Our results demonstrated that the extract of fermented P. macrophylla caused no toxic effects in the rats at the tested doses. Therefore, they may be termed safe for consumption and therapeutic uses.